2015
DOI: 10.1242/dmm.020719
|View full text |Cite
|
Sign up to set email alerts
|

Interplay among transcription factors Ets21c, Fos and Ftz-F1 drives JNK-mediated tumor malignancy

Abstract: Cancer initiation and maintenance of the transformed cell state depend on altered cellular signaling and aberrant activities of transcription factors (TFs) that drive pathological gene expression in response to cooperating genetic lesions. Deciphering the roles of interacting TFs is therefore central to understanding carcinogenesis and for designing cancer therapies. Here, we use an unbiased genomic approach to define a TF network that triggers an abnormal gene expression program promoting malignancy of clonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
101
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(113 citation statements)
references
References 104 publications
(159 reference statements)
10
101
1
Order By: Relevance
“…In the Drosophila adult midgut, Ets21c expression is increased when JNK is activated by the JNK kinase hep (Mundorf et al, 2019). Ets21c also can promote tumor growth downstream of the JNK pathway (Külshammer et al, 2015;Toggweiler et al, 2016). Our results have confirmed that Ets21c functions downstream of JNK.…”
Section: Jnk Signaling Mediates Hpo-activation-induced Cell Extrusionsupporting
confidence: 75%
“…In the Drosophila adult midgut, Ets21c expression is increased when JNK is activated by the JNK kinase hep (Mundorf et al, 2019). Ets21c also can promote tumor growth downstream of the JNK pathway (Külshammer et al, 2015;Toggweiler et al, 2016). Our results have confirmed that Ets21c functions downstream of JNK.…”
Section: Jnk Signaling Mediates Hpo-activation-induced Cell Extrusionsupporting
confidence: 75%
“…8i, j). Inhibition of either JNK or JAK–STAT in Ras V12 scrib −/− tumours reversed ROS accumulation 18 (Fig. 3k, l).…”
mentioning
confidence: 83%
“…The following stocks were provided to us (18) y,w,ey-flp; Act>y + >Gal4, UAS-GFP/CyO; Frt82B, tub-Gal80, (19) y,w;UAS-Ras V12 /CyO; Frt82B/TM6B; (20) y,w; UAS-Ras V12 ,UAS-dome Δcyt2.1 /CyO; Frt82B, scrib 2 /TM6B and (21) UAS-Ras V12 , UAS-upd; Frt82B (T. Xu). (22) UAS-Ras V12 /CyO; Frt82B scrib 1 , UAS-bsk DN /TM6B , (23) w;UAS-ets21c long-RNAi ,UAS-Ras V12 /CyO; Frt82B scrib 1 , UAS-fos 39 / 19RNAi /TM6B , (24) w;UAS-Ras V12 /CyO; Frt82B scrib 1 , kay 3 /TM6B , (25) w;UAS-Ras V12 , exp::LacZ;Frt82B scrib 1 /S-T (M. Uhlirova) 18 , (26) y,w,ey-flp1;act>y+>GFP,UAS-GFP,egr 1 /CyO;FRT82,tub80/TM6B , (27) y,w, eyFLP1; G454, Act>y + >Gal4, UAS-mRFP; FRT82B, Tub-Gal80 (T. Igaki) 27,28 , (28) >Ras,egr 3 /CyO; FRT82B, scrib 1 /TM6B (M. Vidal) 17 , (29) atg13 Δ81 (T. P. Neufeld) 29 , (30) w, upd3 p[XP]d0495 (M. Zeidler), (31) pmCh-atg8a (E. Baehrecke) 6 , (32) UAS-Bsk DN (D. Bohmann), (33) Frt82B stat92E 85C9 (G. Halder), (34) UAS-s.Imp-L2 (E. Hafen) 30 , (35) UAS-dlg RNAi , UAS-Ras V12 (ref. 15), (36) UAS-dp110 D945A (S. M. Cohen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having shown that Defensin restrict tumour growth, we sought to 143 determine the tissues that produced endogenous Defensin in the context of 144 tumour bearing. Previous studies have shown that Defensin is not produced 145 by imaginal discs or tumours (Bunker et al, 2015;Kulshammer et al, 2015). 146…”
Section: Defensin Remotely Produced From Immune Tissues Bind To Tumoumentioning
confidence: 97%